Tuning the Porphyrin Building Block in Self‐Assembled Cages for Branched‐Selective Hydroformylation of Propene. Issue 59 (17th August 2017) - Wang, Xiaowu; Nurttila, Sandra S.; Dzik, Wojciech I.; Becker, René; Rodgers, Jody; Reek, Joost N. H.
Abstract: Unprecedented regioselectivity to the branched aldehyde product in the hydroformylation of propene was attained on embedding a rhodium complex in supramolecular assemblyL2, formed by coordination‐driven self‐assembly of tris( meta ‐pyridyl)phosphine and zinc(II) porpholactone. The design of cageL2 is based on the ligand‐template approach, in which the ligand acts as a template for cage formation. Previously, first‐generation cageL1, in which zinc(II) porphyrin units were utilized instead of porpholactones, was reported. Binding studies demonstrate that the association constant for the formation of second‐generation cageL2 is nearly an order of magnitude higher than that ofL1 . This strengthened binding allows cageL2 to remain intact in polar and industrially relevant solvents. As a consequence, the unprecedented regioselectivity for branched aldehyde products can be maintained in polar and coordinating solvents by using the second‐generation assembly. Abstract : Cage‐controlled catalysis : The self‐assembly of tris( m ‐pyridyl)phosphine and three zinc porpholactone units yields a supramolecular cage that is stable in both nonpolar and polar solvents. Coordination to rhodium(I) affords a catalyst that is capable of unprecedented branched‐selective hydroformylation of propene in industrially relevant solvents (see figure).